Tumor Microenvironment-Mediated Immune Profiles Characterized by Distinct Survival Outcome and Immunotherapeutic Efficacy in Breast Cancer - Xu, Lijun; Hu, Yaomin; Liu, Wenwen (Frontiers in Genetics, 2022)
Background Numerous reports have highlighted that tumor microenvironment (TME) is closely linked to survival outcome and therapeutic efficacy. However, comprehensive investigation of TME feature in breast cancer (BC) has not been performed. Methods Here, we performed consensus clustering analysis based on TME cell expression profiles to construct TME pattern clusters and TME-related gene signature in BC. GSVA combined with CIBERSORT and ssGSEA algorithms were applied to evaluate the differences in biological pathways and immune cell infiltration level, respectively. The PCA method was employed to construct the TME-score to quantify the TME-mediated pattern level in individual BC patient. Results We determined two distinct TME gene clusters among 3738 BC samples, which exhibited distinct survival outcome and enriched biological processes. The TME features demonstrated that these two clusters corresponded to the established immune profiles: hot and cold tumor phenotype, respectively. Based on TME-related signature genes, we constructed TME-score and stratified BC patients into low and high TME-score group. Patients with high TME-score exhibited favorable outcome and increased infiltration of immune cells. Further investigation revealed that high TME-score was also related with high expression of immunosuppressive molecules, decreased tumor mutation burden (TMB) and high rate of mutation in significantly mutated genes (SMGs) (e.g., PIK3CA and CDH1). Conclusions Assessing the TME-mediated pattern level of individual BC patient will assist us in better understanding the responses of BC patients to immunotherapies and directing more effective immunotherapeutic approaches.